TITLE: EFFECTIVE STRATEGIES FOR TEACHING ENGLISH IN PRESCHOOL EDUCATION - Shamsuddinova Diyoraxon Yorqinbek qizi; Mirzaazizova Farangiz (TADQIQOTLAR, 2025)
Abstract Early childhood is a critical period for language development. Integrating English language instruction into preschool education can greatly influence children’s cognitive and linguistic growth. This paper explores practical and developmentally appropriate strategies for teaching English to preschool learners. It emphasizes the importance of play-based and child-centered methods, the use of authentic materials, and the role of the teacher in creating an immersive language environment. Furthermore, the paper underlines the necessity of aligning language instruction with children’s psychological and emotional development. Effective preschool English education not only lays the foundation for future academic success but also nurtures curiosity and positive attitudes towards language learning.